On quadrature and cubature formulas for a class of multiple singular integrals - Akimenko, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We consider the problem of conditions for the existence of multiple singular integrals of a certain class at inner and boundary points of a domain. We obtain the quadrature and cubature formulas for calculating multiple singular integrals and present the corresponding estimates for the formulas.